2008
DOI: 10.1021/jm8010492
|View full text |Cite
|
Sign up to set email alerts
|

An Adamantyl-Substituted Retinoid-Derived Molecule That Inhibits Cancer Cell Growth and Angiogenesis by Inducing Apoptosis and Binds to Small Heterodimer Partner Nuclear Receptor: Effects of Modifying Its Carboxylate Group on Apoptosis, Proliferation, and Protein-Tyrosine Phosphatase Activity

Abstract: Apoptotic and antiproliferative activities of small heterodimer partner (SHP) nuclear receptor ligand (E)-4-[3′-(1-adamantyl)-4′-hydroxyphenyl]-3-chlorocinnamic acid (3-Cl-AHPC), which was derived from 6-[3′-(1-adamantyl)-4′-hydroxyphenyl]-2-naphthalenecarboxylic acid (AHPN), and several carboxyl isosteric or hydrogen bond-accepting analogues were examined. 3-Cl-AHPC continued to be the most effective apoptotic agent, whereas tetrazole, thiazolidine-2,4-dione, methyldinitrile, hydroxamic acid, boronic acid, 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(48 citation statements)
references
References 15 publications
0
48
0
Order By: Relevance
“…More studies are warranted about whether miR-421 can regulate FXR by targeting 5 0 -UTR or ORF of FXR mRNA. Besides involved in the regulation of bile acid, lipid, and glucose metabolisms, recent studies have shown that FXR can protect against tumorigenesis and inhibit cell growth in several cancers including HCC (23)(24)(25). Usually, FXR regulates cell proliferation and/or apoptosis through the function of its target genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More studies are warranted about whether miR-421 can regulate FXR by targeting 5 0 -UTR or ORF of FXR mRNA. Besides involved in the regulation of bile acid, lipid, and glucose metabolisms, recent studies have shown that FXR can protect against tumorigenesis and inhibit cell growth in several cancers including HCC (23)(24)(25). Usually, FXR regulates cell proliferation and/or apoptosis through the function of its target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, FXR regulates cell proliferation and/or apoptosis through the function of its target genes. For example, SHP, a typical target gene of FXR, has been shown to suppress cell proliferation and promote apoptosis (23). It is reported that the expression of SHP was downregulated in human HCC, and mice with SHP deficiency developed spontaneous liver tumors (24,26).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous ARR analogues have been synthesized and the associated efficacy studies have shown that the presence of the 4′-hydroxyl group, the 3′-(1-adamantyl group), and the carboxylic group is essential for the induction of apoptosis by these compounds (43). The ability of these compounds to bind to SHP and modify the biological activity of SHP and the fact that loss of SHP expression markedly inhibits ARR-mediated apoptosis strongly suggest that SHP functions as the receptor through which the ARRs exert their apoptotic activities.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, synthetic retinoidlike compounds such as 3-Cl-AHPC have been shown to bind and regulate SHP activity (34)(35)(36). We speculate that binding of these pharmacophores might rearrange the kinked helix H10, thus allowing formation of the AF-2 cofactor-binding pocket.…”
Section: Arillmastlknipgtllvdlffrpimgdvditelledmlllr-aelnsalfllrfinsdmentioning
confidence: 92%
“…SHP-mediated repression is abolished in mice lacking FGF15, leading to abnormally high levels of CYP7A1 expression and fecal bile acid excretion (33). A number of retinoid-like compounds have been shown to bind to SHP and enhance its repression of CYP7A1 and CYP8B1 in liver cells (34)(35)(36). These findings underscore the importance of understanding the functional and structural basis for SHP's inhibitory function, which could serve as a drug target for treating metabolic diseases arising from bile acid and cholesterol imbalances.…”
Section: Significancementioning
confidence: 99%